Multifactorial analysis of patient dissatisfaction after TKR – the influence of psychological factors. Issue 5 (31st May 2017) - Fritsch, Brett A; Dhurve, Kunal; Scholes, Corey; El-Tawil, Sherif; Molloy, Allan; Parker, David A.; Coolican, Myles
Objectives: The published rates of dissatisfaction following total knee replacement (TKR) range between 11-18%, with residual symptoms and psychological distress being important features. The aims of this study were to identify the prevalence and causes of dissatisfaction in a cohort of private practice patients, and to describe a post-operative management program which may improve satisfaction with their replaced knee in these patients. Methods: A cohort of 375 patients with unilateral TKR was evaluated to identify patients who were dissatisfied with TKR. Dissatisfied and satisfied patients were matched in terms of age, gender, follow-up duration and BMI. Psychological evaluation was performed using the pain catastrophizing scale (PCS), Depression, Anxiety and Stress Scale (DASS) and the Multidimensional Health Locus of Control (MHLC) scale. The pre and post-operative Oxford knee scores (OKS) and range of motion (ROM), preoperative grade of osteoarthritis, and prevalence of comorbidities were also compared between groups. Patients indicating dissatisfaction with their TKR were then followed up by phone on a second occasion 12months later. Those that indicated enduring dissatisfaction were invited to participate in a chronic pain program utilising cognitive behavioural therapy, desensitisation and coping strategies. Patients referred to the program were screened by the therapists for inclusion and enrolled into a flexible course of therapy. Pre- and post- intervention questionnaires will be used to determine the effect of the program on satisfaction rates (5-point Likert scale) and psychological responses to pain. Results: The final cohort consisted of 301 patients (response rate 80%), with 24 patients (6.5%) dissatisfied with the result of TKR. Persistent pain was the most common reason for dissatisfaction (n=10). Dissatisfied patients reported a significantly (P = 0.03) higher mean PCS score (mean±SD, 11.3±10.3), compared to satisfied patients (5.4±6.3) and a significantly (P = 0.02) higher depression component of the DASS (3.5±3.3 vs 1.4±1.6). In addition, dissatisfied patients returned a significantly (P = 0.02) lower internal locus of control (16.6±8.2 vs 21.3±8.2). The dissatisfied group also exhibited a reduced improvement in the OKS and ROM, as well as a lower preoperative grade of osteoarthritis compared to satisfied patients. Preliminary analysis revealed that five patients (21%) became satisfied with their knee despite no intervention occurring between measurements. Of the remaining patients, five patients (21%) did not think their ongoing issues were severe enough to warrant further intervention, and nine patients (38%) were referred directly to the program. It is expected that these results will shed new light on the potential management options for these patients that identify as dissatisfied after a primary unilateral TKR. Conclusion: Dissatisfied patients exhibit higher scores for catastrophisation and depression, with lower self confidence in managing their knee symptoms. In addition, they have lesser improvements in the OKS and ROM. Thus, both physical as well as psychological factors contribute to dissatisfaction. Identification of these factors can help in planning focused interventions to address dissatisfaction. This is the longest follow-up of such a cohort; our results so far indicate that 21% of such patients can improve spontaneously with time which challenges some conventional beliefs. The results of the 38% of patients who remain dissatisfied and will undergo the program will determine whether such an intervention will be worthwhile in this difficult clinical situation.